2011
DOI: 10.1103/physrevb.84.075161
|View full text |Cite
|
Sign up to set email alerts
|

Mott physics and first-order transition between two metals in the normal-state phase diagram of the two-dimensional Hubbard model

Abstract: For doped two-dimensional Mott insulators in their normal state, the challenge is to understand the evolution from a conventional metal at high doping to a strongly correlated metal near the Mott insulator at zero doping. To this end, we solve the cellular dynamical mean-field equations for the two-dimensional Hubbard model using a plaquette as the reference quantum impurity model and continuous-time quantum Monte Carlo method as impurity solver. The normal-state phase diagram as a function of interaction stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
137
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(149 citation statements)
references
References 116 publications
(215 reference statements)
12
137
0
Order By: Relevance
“…Recent CDMFT calculations using 2×2 plaquettes have found a similar pseudogap phase diagram, with a transition at low doping between two metallic phases involving a change of FSs [323,324]. In these pure Hubbard model (t = 0) calculations, the small FS-metal at low doping plays the role of the doped (π, π) SDW-metal found in DCA [63], and the large FS-metal corresponds to the nonmagnetic state.…”
Section: Role Of Vhsmentioning
confidence: 75%
See 3 more Smart Citations
“…Recent CDMFT calculations using 2×2 plaquettes have found a similar pseudogap phase diagram, with a transition at low doping between two metallic phases involving a change of FSs [323,324]. In these pure Hubbard model (t = 0) calculations, the small FS-metal at low doping plays the role of the doped (π, π) SDW-metal found in DCA [63], and the large FS-metal corresponds to the nonmagnetic state.…”
Section: Role Of Vhsmentioning
confidence: 75%
“…This interpretation is suggested by a number of factors: (1) Figure 9 of Ref. [324] shows the effective chemical potentials at three k-points vs doping and Hubbard energy U . For (π, 0), corresponding to the VHS, µ ef f crosses [330].…”
Section: Role Of Vhsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Sordi et al have shown that doublet formation (total spin S = 1/2) in a one-band Hubbard model grows upon doping the parent Mott insulator. 51 The same is true of the S = 1/2 three-spin polaron present in three-band models, 52,53 where the spin of a hole on the in-plane oxygen is antiparallel to the two nearest-neighbor copper spins. However, the hole in these and the triplet state (total spin S = 1) is mobile, with the effective magnetic moment presumably fluctuating too fast to cause dynamic depolarization of the TF-µSR signal.…”
Section: Discussionmentioning
confidence: 90%